2015
DOI: 10.1177/0042098015576861
|View full text |Cite
|
Sign up to set email alerts
|

Hukou-based labour market discrimination and ownership structure in urban China

Abstract: This paper utilises a 2008 survey on the wave of rural-urban migration in China to provide new empirical evidence on labour market discrimination against rural-to-urban migrants with rural hukou in two ownership sectors within urban China: state-owned enterprises and private firms. By employing a double-selectivity approach, this study shows that the high-wage state-owned enterprise sector is more discriminatory than the private sector against rural hukou holders in urban China. Furthermore, the results from q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 30 publications
1
33
0
5
Order By: Relevance
“…With scarce land resources in the city, some real estate developers scramble for resources by bidding the highest prices based on optimistic growth forecasts in land prices or on their reputation in the real estate industry. At the same time, due to the restriction of the Chinese household registration system, settling down in an urban area is considered desirable and worthy of pursuing for modern amenities or better education for children [19,58]. Consequently, these actions will drive the land prices up.…”
Section: Relationship Between Land Price and Immigrant Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…With scarce land resources in the city, some real estate developers scramble for resources by bidding the highest prices based on optimistic growth forecasts in land prices or on their reputation in the real estate industry. At the same time, due to the restriction of the Chinese household registration system, settling down in an urban area is considered desirable and worthy of pursuing for modern amenities or better education for children [19,58]. Consequently, these actions will drive the land prices up.…”
Section: Relationship Between Land Price and Immigrant Populationmentioning
confidence: 99%
“…The trend of immigration from rural areas to urban areas has significantly been influenced by the implementation of the household registration system (hukou). Although some studies have discussed the reforms of China's "hukou" system from the perspectives of social inequality [58], labor market discrimination [19] and so on, more attention should be given to short-and medium-term prospects of reform in hukou, which could help to ease the pressures associated with the problems of migrant workers from rural areas and the real estate inventory. The proposed in-situ urbanization strategy highlights the development of until now undeveloped countryside.…”
Section: Potential Strategies On Residential Land Price Managementmentioning
confidence: 99%
“…Around 28 per cent of this difference could not be explained by observable characteristics. A more recent paper draws on the 2008 wave of the Rural-Urban Migration in China (RUMiC) survey to provide fresh empirical evidence on labour market discrimination against rural-to-urban migrants with rural hukou (Song, 2016). This shows that the average monthly earnings of urban hukou holders and rural migrants working in cities were 2,194 and 1,506 yuan, respectively.…”
Section: Hukou-based Labour Market Discrimination In Urban Chinamentioning
confidence: 99%
“…Similarly, Ge (2014) found that average wages were about 9 per cent higher in unionized firms than in non-unionized firms, after controlling for other firm characteristics and industry and regional effects. Finally, a very recent paper reconciles the two strands of literature on the role of the Chinese unions by exploring the heterogeneous effects of unionization on wages in firms with and without political connections (Song, Yang and Yang, 2016). Its authors draw on a survey of 1,268 firms in 12 cities to verify the hypothesis that wages increase with unionization, but they also find the union wage effect to be significantly dependent on firms' political connections.…”
Section: Trade Unionsmentioning
confidence: 99%
“…Quelque 28 pour cent de cette différence ne peuvent s'expliquer par des caractéristiques observables. Un article plus récent s'appuie sur la vague 2008 de l'Enquête sur la migration campagne-ville en Chine (RUMiC) pour apporter de nouvelles preuves empiriques de la discrimination exercée à l'encontre des migrants détenteurs d'un hukou rural qui vont travailler dans les villes (Song, 2016). Selon cet article, les revenus mensuels moyens des détenteurs d'un hukou urbain et des migrants ruraux travaillant dans les villes étaient de 2 194 et de 1 506 yuan, respectivement.…”
Section: Discrimination Fondée Sur Le Hukou En Milieu Urbainunclassified